Expanding the Obesity Research Paradigm to Reach African American Communities - Shiriki K. Kumanyika, PhD, MPH; Melicia C. Whitt-Glover, PhD; Tiffany L. Gary, PhD; T. Elaine Prewitt, DrPH; Angela M. Odoms-Young, PhD; Joanne Banks-Wallace, RN, PhD; Bettina M. Beech, DrPH, MPH; Chanita Hughes Halbert, PhD; Njeri Karanja, PhD; Kristie J. Lancaster, PhD, RD; Carmen D. Samuel-Hodge, PhD (Centers for Disease Control and Prevention, 2007)
Obesity is more prevalent among African Americans and other racial and ethnic minority populations than among whites. The behaviors that determine weight status are embedded in the core social and cultural processes and environments of day-to-day life in these populations. Therefore, identifying effective, sustainable solutions to obesity requires an ecological model that is inclusive of relevant contextual variables. Race and ethnicity are potent stratification variables in U.S. society and strongly influence life contexts, including many aspects that relate to eating and physical activity behaviors. This article describes a synthesis initiated by the African American Collaborative Obesity Research Network (AACORN) to build and broaden the obesity research paradigm. The focus is on African Americans, but the expanded paradigm has broader implications and may apply to other populations of color. The synthesis involves both community and researcher perspectives, drawing on and integrating insights from an expanded set of knowledge domains to promote a deeper understanding of relevant contexts. To augment the traditional, biomedical focus on energy balance, the expanded paradigm includes insights from family sociology, literature, philosophy, transcultural psychology, marketing, economics, and studies of the built environment. We also emphasize the need for more attention to tensions that may affect African American or other researchers who identify or are identified as members of the communities they study. This expanded paradigm, for which development is ongoing, poses new challenges for researchers who focus on obesity and obesity-related health disparities but also promises discovery of new directions that can lead to new solutions.